EFEKTIVITAS PENERAPAN PENILAIAN OTENTIK PEMBELAJARAN BAHASA INDONESIA UNTUK PENINGKATAN KINERJA ILMIAH SISWA - Nusrotus Sa’idah; Hayu Dian Yulistianti; Yushinta Eka Farida (Universitas Muria Kudus, 2017)
The aims of the study are to determine the effectiveness of three authentic assessments appilcations, there are project appraisal, performance appraisal and portfolio assessment. The methodelogy used in this research is experimental study that used three classes of sampling and each class used different treatment of authentic assessment. The sample of the research is the students of class X in MA Darul Ulum Purwogondo Jepara with random sampling. This research is preceded by requirement data test that is homogeneity test p-value 0,163 as a result which showed sample taken identical because more than sig 0,05. The results show that there is a difference in the mean value of three authentic assessment apps with p-value 0.00. Among the three assessments the most effective is the portfolio assessment with the mean difference showing the value of 3.371.Therefore, authentic assessment is very effective in learning to improve students' scientific performance.